2019
DOI: 10.1136/bmjpo-2018-000385
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonic and isotonic intravenous maintenance fluids in hospitalised paediatric patients: a randomised controlled trial

Abstract: ObjectiveTo compare the changes in serum sodium and acid/base status in patients receiving hypotonic and isotonic solutions.DesignA randomised, controlled and double-blind clinical trial.SettingDepartment of Paediatrics in a tertiary general hospital (Hospital Universitario Austral) in Buenos Aires, Argentina.PatientsChildren between 29 days and 15 years of age who were hospitalised in the paediatric intensive care unit and general hospital between 12 January 2010 and 30 November 2016, and who required exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…Several well-conducted randomized controlled trials have shown that isotonic fluids are effective in preventing the development of mild or moderate hyponatremia in acutely ill children receiving maintenance fluid therapy [1][2][3][4]. Accordingly, the American Academy of Pediatrics (AAP) has recommended the use of isotonic maintenance fluid therapy to prevent hyponatremia in children [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several well-conducted randomized controlled trials have shown that isotonic fluids are effective in preventing the development of mild or moderate hyponatremia in acutely ill children receiving maintenance fluid therapy [1][2][3][4]. Accordingly, the American Academy of Pediatrics (AAP) has recommended the use of isotonic maintenance fluid therapy to prevent hyponatremia in children [1].…”
Section: Introductionmentioning
confidence: 99%
“…One study specifically looking into this outcome was included in our analysis. In a study conducted by Torres et al [ 61 ], there were no significant differences in the incidence of metabolic acidosis between the two treatment arms ( Figure 4 and Figure S5 ). Other studies have found that isotonic fluid causes metabolic acidosis, but many of them involved rapid fluid infusion [ 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 85%
“…The causes could be related to the administration of anesthetic agents or opioids and the non-osmotic secretion of ADH (22)(23)(24). In patients recovering from abdominal surgery, excessive interstitial fluid immediately after the procedure as well as the presence of colostomies (with possible sodium loss) could also explain this association (16).…”
Section: Discussionmentioning
confidence: 99%
“…These diuretics can cause volume depletion, or the patient may receive a high supply of fluids which is poorly tolerated by the children because loop diuretics may partially alter the ability to dilute the urine. These effects may be more frequent in very small children, who also have difficulties in maintaining a hypertonic renal medulla ( 16 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation